The Structure of Multinational Firms' International Activities - Ronald B. Davies; James R. Markusen (Center for Economic Studies and ifo Institute (CESifo), 2020)
The structure of a multinational firm, that is how its affiliates relate to one another, is critical for understanding where multinationals locate, how policy affects them, and their resilience to localized shocks. Here, we review the two main structures: horizontal investments which replicate activities across borders, and vertical investments which fragment activities across countries. In addition, we use data (primarily from the US) to examine which of these structures seems to dominate the data. This includes a novel use of measures of global value-chain positioning of a country's industries. In each case, the data suggests a dominant role for horizontal investment. We conclude with a discussion of the challenge that intangibles play in multinational data and point towards potentially fertile areas for future research.
Keywords: F23; 330; horizontal multinationals; vertical multinationals; replication; fragmentation